1999
DOI: 10.1152/jappl.1999.86.5.1497
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon emulsion improves oxygenation of the cat primary visual cortex

Abstract: Tissue PO2 was measured in the primary visual cortex of anesthetized, artificially ventilated, normovolemic cats to evaluate the effect of small doses [1 g perfluorocarbon (PFC)/kg] of a PFC emulsion (1 g PFC/1.1 ml emulsion; Alliance Pharmaceutical, San Diego, CA) on brain oxygenation. The change in tissue PO2 (DeltaPO2), resulting from briefly changing the respiratory gas from room air to 100% oxygen, was measured before and after intravenous infusion of the emulsion. Before emulsion, DeltaPO2 was 51.1 +/- 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Increases in cerebral ptiO 2 in normal brain have been demonstrated with a similar but more concentrated PFC emulsion from Alliance (AF0104; 0.9 g perflubron/1.0 ml) administered with short periods of 100% O 2 (36). Instead of a series of O 2 challenges, however, the current study used 100% O 2 during the entire treatment phase of the study to model its use in the critical care setting, where extended increases in the fraction of inspired oxygen may be appropriate in patients with critically low cerebral ptiO 2 (30,31).…”
Section: Tissue Oxygen Tensionmentioning
confidence: 85%
See 1 more Smart Citation
“…Increases in cerebral ptiO 2 in normal brain have been demonstrated with a similar but more concentrated PFC emulsion from Alliance (AF0104; 0.9 g perflubron/1.0 ml) administered with short periods of 100% O 2 (36). Instead of a series of O 2 challenges, however, the current study used 100% O 2 during the entire treatment phase of the study to model its use in the critical care setting, where extended increases in the fraction of inspired oxygen may be appropriate in patients with critically low cerebral ptiO 2 (30,31).…”
Section: Tissue Oxygen Tensionmentioning
confidence: 85%
“…With the addition of PFCs, however, the transport of O 2 can be expanded to the entire surface area of the capillary (36). Under normal conditions, most capillaries are perfused by a "single file" column of RBCs known as rouleaux with limited O 2 transport by the plasma.…”
Section: Tissue Oxygen Tensionmentioning
confidence: 99%
“…Braun et al 19 showed that there was no change in retinal oxygen consumption after administration of perflubron emulsion. Padnick et al 20 found that the infusion of perflubron emulsion had no effect on systemic hemodynamics, cerebral blood flow, or cortical electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Perflubron emulsion (5.4 g PFC/kg) has been shown to significantly increase brain cortex oxygen tension in unanesthetized rabbits breathing 100 percent oxygen 22 . Padnick et al 20 showed that the infusion of perflubron emulsion (1 g PFC/kg) and 100 percent oxygen significantly increased tissue oxygen tension in the primary visual cortex of anesthetized normovolemic cats.…”
Section: Discussionmentioning
confidence: 99%
“…Perfluorocarbon with high affinity to oxygen has been demonstrated as promising O 2 shuttle to fight against hypoxic intratumor microenvironment so as to enhance the efficacy of some treatments such as RT and PDT. It is well known that PDT is strongly oxygen dependent because the PDT‐induced single oxygen ( 1 O 2 ) typically originates from oxygen molecules, which means that the therapeutic efficacy of PDT is substantially hindered by the tumor hypoxia .…”
Section: Oxygen (O2)‐generating Ggnsmentioning
confidence: 99%